Pengembangan Modul Numerasi Materi Pengukuran Panjang (Monupa) Berbantuan Kodular terhadap Kemampuan Numerasi Siswa Sekolah Dasar - Fauziah, Nurlaili; Wardhani, Dyah Ayu Pramoda (IAIN Kendari, 2025)
Numeracy skills are essential foundational competencies that must be mastered from the elementary school level. However, students' low interest in mathematics and high dependency on digital devices pose challenges that require innovative solutions. This study aims to develop and evaluate the effectiveness of the Numeracy Module on Length Measurement (Monupa), supported by Kodular, as a contextual, interactive learning solution aligned with students’ digital habits. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The module's validity was assessed by content and media experts and implemented among second-grade elementary students. The findings revealed that Monupa is highly valid (100% and 92%) and effectively enhances students' numeracy skills, with an average N-Gain score of 0.16. The highest improvement was observed in students' understanding of using numbers in length measurement. The module was considered user-friendly and engaging, demonstrating potential to boost students' active participation. This development strengthens the integration of mobile technology with numeracy learning strategies grounded in real-life contexts. Monupa contributes to innovative Android-based learning media that are responsive to the demands of 21st-century elementary education.Keywords: Elementary numeracy module; length measurement; Android-based learning; Kodular; student numeracy literacy